Health Commodities Management Systems and Service Delivery in Selected Level 4 Public Hospitals - Ogollah, Hellen Anyango (JOOUST, 2023)
Service delivery interruptions are frequently recorded in public hospitals in Kenya despite huge expenditure and expertise of the health workforce in healthcare system. This has led to spread of communicable diseases during outbreaks, disabilities and deaths amongst the patients seeking medical attention in these hospitals. The main objective of this study was to assess the relationship between health commodities management systems and service delivery in relation to available health policies and guidelines fat the selected level 4 public hospitals in Lake Region Economic Bloc (LREB), Kenya. To achieve this, the study assessed four health commodities management systems of information systems infrastructure, health procurement processes, inventory control techniques and storage mechanisms used at the hospital warehouse and unit stores of the casualty, laboratory and pharmacy. The target population was 99 level 4 public hospitals with NHIF codes within ten counties of the region and 426 respondents. The hospitals were sampled using stratified sampling technique giving a sample size of 79 public hospitals which was calculated using Yamane formula. Purposive sampling technique was used for the respondents both at the county health management team and hospital levels giving a sample size of 346 respondents. The respondents included nursing officers, medical laboratory technologists, pharmaceutical officers and warehouse personnel handling health commodities at the hospitals plus health administrators, finance officers and supply chain management officers at the county health management team in each county. Data collection instruments were structured questionnaires, observation checklists and interview schedules whose reliability and validity were tested appropriately. Descriptive and inferential statistics were used to analyze the collected data which was presented in tables as was appropriate in the study. The study found an R2 value of 0.899 and p=0.000 which implied that 89.9% of the variation in service delivery at level 4 public hospitals in the region could be attributed to information systems infrastructure, procurement processes, inventory control techniques and storage mechanisms. The study concluded that health commodities management systems as described by the health policies and guidelines are key determinants of service delivery in level 4 public hospitals. The study recommended appropriate dissemination and implementation of the available relevant health commodities management policies and guidelines to promote availability and accessibility to health commodities at level 4 public hospitals and also creation of active Health Commodities Management unit composed of officers with knowledge and skills on health logistics and supply chains management in the hospitals.
Keywords: Service Delivery; Level 4 Public Hospitals; Health Commodities; Management Systems